The Role of Information Systems in Enhancing Strategic Decision Making: A Review and Future Directions - Dhiraj Kumar Akula; Yaseen Shareef Mohammed; Asif Syed; Gazi Mohammad Moinul Haque; Yeasin Arafat (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
In the digital change era, organizations are becoming more dependent on Information Systems (IS) as part of the implementing strategic decision making throughout various levels of operation. The paper gives a formal, evidence-based literature overview to explore the ways in which IS helps to make better, faster and more optimal decisions with respect to long-term business perspectives. Based on peer-reviewed research of more than 80 studies using approved academic sources like Scopus, IEEE Xplore, and ScienceDirect, and Wiley-Online Library, the review summarizes analyzed scholarly literature of the past ten years. This paper classifies IS types, which include Decision Support System (DSS), Executive Information System (EIS), Enterprise Resource Planning (ERP) and Business Intelligence (BI) system, based on their strategic capabilities. Quantitative factors including reduction in the cycle time of decisions, return on investment in information technology as well as the ability to predict were measured to gauge IS effectiveness. Due to research findings, there is positive and constant relationship between adoption of IS and improvement of strategic performance outcomes in various sectors such as healthcare, manufacturing, finance, and retail. Yet there are a number of obstacles which still remain such as barriers of integration, opposition to digital culture and inability in decision makers to possess adequate analytical skills. The paper has identified such constraints and provided an organizational readiness framework of strategic IS integration. Additionally, it demonstrates upcoming horizons like AI-helped IS, real-time analytics, and morality IS governance as potential ardent research facilities in the future. The uniqueness of the study consists in its integrative comprehensive analysis of disparate knowledge, as well as the creation of the prospective agenda of matching IS potential with strategic organizational goals. The review contains practical suggestions to the business leaders, IT strategists, and policy makers who are willing to derive business competitive advantage out of IS..